Praktik Akad Pembiayaan Gadai Emas Perspektif Hukum Islam - Kholid , M (LPPPM STAI Darul Hikmah Bangkalan, 2018)
This study aims to: 1) Know more about the practice of gold pawn financing at BMT-UGT Sidogiri Kwalanar Bangkalan Branch Office. 2) to know the contract of the golden installment of the gold mortgage at BMT-UGT Sidogiri Kwanyar Bangkalan Sub-Branch Office according to the Islamic Law. Analysis of the data obtained from the research is that it can be stated that: 1) Basically gold pawning on BMT-UGT Sidogiri Kwanyar Bangkalan Sub-Branch Office has fulfilled the conditions and conditions according to muamalah fiqih. 2) Islamic banks that should adjust themselves to the principles of Shari'ah, in BMT-UGT Sidogiri Kwalanar Bangkalan Sub-Branch Office is still weak in that matter so that it can cause invalid contract. 3) In the case of history; Determination of administrative costs, place rent, and estimated goods of Sidogiri BMT-UGT are still less prioritizing the participation of both parties so that they are still considered unilateral decisions and not in accordance with the provisions of Islamic law contained in the words of Allah SWT QS al-Baqarah 2 : 275,278-280, and Surah an-Nisa '4:29